A general framework for Learning Analytic in a Smart Classroom - Cordero Zambrano, J. (2016)
n this paper we propose the utilization of the Learning Analytics paradigm in a Smart Classroom. Learning Analytics can extract knowledge from a Smart Classroom platform to better understand students and his/her learning processes. In this way, a Smart Classroom can understanding and optimizing the learning process and the teaching environments proposed. The smart classroom can adapt its components to improve students performance, among others. Particularly, this paper proposes a framework about how Learning Analytics paradigm can be used in a Smart Classroom, in order to provide knowledge about the activities taking place within it. The framework is defined like a closed cycle of Learning Analytics tasks, which generate metrics used like feedback to optimize the pedagogical model proposed by the smart Classroom. The metrics evaluate the learning process and pedagogical practice provided by the smart Classroom.